The Role of Social Studies Teachers in Reinforcing Social Values to Prevent Student Fights - Harianda, Jaka Rizkiawan; Asiyah; Gilang, M. Ilham (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Education is the cornerstone of developing human resources who are not only academically excellent but also possess good character and social behaviour. Instilling these values is crucial in preventing conflicts, particularly fights between pupils within the school environment. Therefore, the role of teachers, particularly Social Studies teachers, is highly strategic in shaping and reinforcing social values among pupils. This study aims to: (1) describe the role of Social Studies teachers in reinforcing social values in Year 9 at SMPN 06 Seluma, and (2) describe the social values instilled by Social Studies teachers to prevent conflicts and fights among students. The research method employed was a qualitative approach, with data collection techniques including interviews, observation, and documentation. Research findings indicate that the role of social studies teachers in reinforcing social values is crucial in shaping pupils’ social behaviour and preventing conflicts and fights. This role is manifested through five key functions: as educators, mentors, motivators, evaluators, and facilitators. Teachers do not merely deliver lesson content, but also instil values through setting a good example, fostering habits, providing guidance, offering motivation, and monitoring pupils’ behaviour.